USING DIGITAL DICTIONARY ON STUDENT CREATIVE WRITING IN ENGLISH SUPPLEMENTARY SUBJECT - Nasrullah Nasrullah; Moh Hafidz (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
Abstract: This study explored how digital dictionaries can support students in their creative writing efforts during English supplementary classes at a private senior high school in Indonesia for the 2024–2025 academic year. Targeting 11th-grade students, the research aimed to illustrate the usage of digital dictionaries and their impact on vocabulary growth, writing fluency, and creativity. To gather data, the researchers conducted classroom observations, semi-structured interviews, and analyzed students’ written work. The observations showed that while printed dictionaries were useful for practicing alphabetical order and careful word choice, students favored digital dictionaries for their speed, convenience, and contextual examples. Interviews revealed benefits like boosted confidence and independence, although challenges such as selecting the right word meaning persisted. The data were analyzed through reduction, display, and drawing conclusions, with findings compared to earlier studies. The results suggest that using digital dictionaries to search for, apply, and revise words really boosted students' vocabulary, fluency, and independence. It sparked their creativity, encouraged self-correction, and built their confidence, all while minimizing errors and promoting engaging, thoughtful, and contextual creative writing.